(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This paper examines the functioning of Lok Adalat inmaking inexpensive, efficacious and speedy justice accessible to the public.The Constitution of India guarantees ’Right to Constitutional Remedies’ as afundamental light. The government provides free legal aid to the needy.However, m a country of continental dimensions and with population more than abillion, it becomes very difficult to provide free legal aid to everyone. TheNational Legal Services Authority (NALSA) is trying to spread ’legal literacy’which is a step more than ’literacy’. People care about then rights much morewhen they are aware and are ’legal literate’. Efforts are also being done atprovincial level. The paper particularly examines the role of NALSA and otherState Legal Services Authority which are the key institutions in the gapbetween public and judicial system. The author has personal experiencesregarding the same. All these efforts seem to be a small drop in the ocean,but small drops make mighty oceans. How can these be replicated in other partsof Indiaand similar models developed and adopted in Asia-Pacific countries is a goodresearch area. Such models shall curb conflicts and bring more peace in society- not only in domestic sense but also internationally.